G protein-coupled receptor 40 activation ameliorates dextran sulfate sodium-induced colitis in mice via the upregulation of glucagon-likepeptide-2 - Shinichi Kato; Daichi Utsumi; Kenjiro Matsumoto (Elsevier, 2019)
G protein-coupled receptor (GPR) 40 is a receptor for long-chain free fatty acids that enhances glucagon-like peptide (GLP)-2 production in intestinal L-cells. GLP-2 and its analogs have reported to increase remission rates in patients with Crohn's disease and improve experimental colitis in rodents. In the present study, we investigated the ameliorative effect of GPR40 activation in a dextran sulfate sodium (DSS)-induced murine colitis model using a specific GPR40 agonist, AS2034178. The daily administration of AS2034178 attenuated DSS-induced increases in the disease activity index, the shortening of the colon length, and the histological colonic injury, and increased the myeloperoxidase (MPO) activity and expression of inflammatory cytokines, in a dose-dependent manner. These effects were abolished by treatment with DC260126, a GPR40 antagonist, or GLP-2 (3-33), a GLP-2 antagonist. GPR40 was expressed in the colonic mucosa, which was colocalized with proglucagon, a precursor of GLP-2. AS2034178 significantly increased the amount of GLP-2 in the colonic tissue, which was abolished by DC260126 but not GLP-2 (3-33). Furthermore, AS2034178 significantly promoted the healing of DSS-induced colitis. These findings suggest that GPR40 activation ameliorates DSS-induced colitis in mice by enhancing GLP-2 production. Thus, GPR40 is a potential target for the treatment of IBD. Keywords: G protein-coupled receptor 40 (GPR40), Colitis, Glucagon like peptide-2 (GLP-2), Dextran sulfate sodium (DSS), Inflammatory cytokines